When hens crow : the woman's rights movement in antebellum America - Hoffert, Sylvia D. (Bloomington : Indiana University Press, 1995)
"In 1852 the New York Daily Herald described leaders of the woman's rights movement as "hens that crow." Using speeches, pamphlets, newspaper reports, editorials, and personal papers, Hoffert discusses how ideology, language, and strategies of early woman's rights advocates influenced a new political culture grudgingly inclusive of women. She shows the impact of philosophies of republicanism, natural rights, utilitarianism, and the Scottish Common Sense School in helping activists move beyond the limits of Republican Motherhood and the ideals of domesticity and benevolence." "When Hens Crow also illustrates the work of the penny press in spreading the demands of woman's rights advocates to a wide audience, establishing the competency of women to contribute to public discourse and public life."--Jacket.
The advocates -- The ideology -- The language -- The strategy -- the responses.
Includes bibliographical references (pages 123-147) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Women's rights -- United States -- History -- 19th century; Women -- Political activity -- United States -- History -- 19th century; Feminism -- United States -- History -- 19th century; Language and languages -- Sex differences; Femmes -- Activité politique -- États-Unis -- Histoire -- 19e siècle.; Féminisme -- États-Unis -- Histoire -- 19e siècle.; Langage et langues -- Différences entre sexes; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminism; Language and languages -- Sex differences; Women -- Political activity; Women's rights; United States; Frauenbewegung; USA; Vrouwenbeweging; Gelijke behandeling; Gender Studies & Sexuality; Gender & Ethnic Studies; Social Sciences; Geschichte 1848-1861.; 1800-1899; History